Dampak Promosi Terhadap Kepuasaan Nasabah PT. Allianz Life Indonesia Dengan Kepercayaan Sebagai Variabel Mediasi - Rosida, Rosida; Nainggolan, Benhart (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2022)
This study aims to see and analyze the impact of advertising on satisfaction and trust as a mediating variable at Allianz Life Indonesia Insurance in the city of Tebing Tinggi. The effects we want to know are the direct and indirect effects. This type of explanatory research explains the causal relationship between variables through hypothesis testing. The survey method used is quantitative and uses SmartPLS (Partial Least Square) software version 3.3.3. consists of two sub-models, namely the measurement model (external model) and the structural model (internal model). Random sampling technique when taking samples of up to 97 respondents with the Cochran formula. The research results show that promotion affects customer trust and satisfaction, trust does not affect satisfaction, and trust cannot mediate promotion towards customer satisfaction